Diagnostic Challenges of Lymphoblastic Lymphomas of the Mediastinum - Mlika, Mona; Khanfir, Donia; Braham, Emna; Meddeb, Balkiss; Mezni, Faouzi (Current Respiratory Medicine Reviews, 2019)
Background: Lymphoblastic lymphomas (LL) of the mediastinum are rare tumours that present a challenging diagnosis. The positive diagnosis is based on microscopic findings. Our aim was to highlight the diagnostic difficulties in such situations. Methods: We conducted a descriptive retrospective study including 31 patients presenting mediastinal LL. Results: Radiologic features consisted in all cases in a mediastinal infiltrating mass. Microscopic examination showed in all cases a crowded tumour with many artefacts made of diffuse tumour cells. Immunohistochemial study was performed in all cases. It was quite difficult to interprete in the samples used for extemporaneous examination and repeated in 10 cases. Conclusion: The diagnosis of LL is based on the microscopic examination which is usually performed on small samples with crowding artefacts. Thus, this pathology must be managed by a trained team that is used to deal with such a specimen in order to avoid repeating the biopsy and inducing diagnostic delay.
Keywords: patology